12 + 42 + 72 + . . . + (3n - 2)2 = n(6n^2-3n-1)/2
by induction:
1. show it to be true for n = 1
LS = 12\
please show me how to do this...
A statement Sn about the positive integers is given. Write statements S1, S2, and S3, and show that each of these statements is true. Show your work.��Sn: 12 + 42 + 72 + . . . + (3n - 2)2 = n(6n^2-3n-1)/2
Also, please show me how to prove the statements are true.
2 answers
not on my usual computer, and hit the wrong return key
LS = 12
RS = 1(6-3-1)/2
= not = LS
check your typing,
I assume your general term is (3n-2)^2
which produces the sequence:
1 + 16 + 49 + ...
which is not your series
LS = 12
RS = 1(6-3-1)/2
= not = LS
check your typing,
I assume your general term is (3n-2)^2
which produces the sequence:
1 + 16 + 49 + ...
which is not your series